There and Back Again: Women's Marginal Commuting Costs - Annette Bergemann; Stephan Brunow; Isabel Stockton (Institute of Labor Economics (IZA), 2024)
We estimate female and male workers' marginal willingness to pay to reduce commuting distance in Germany, using a partial-equilibrium model of job search with non-wage job attributes. Commuting costs have implications not just for congestion policy, spatial planning and transport infrastructure provision, but are also relevant to our understanding of gender differences in labour market biographies. For estimation, we use a stratified partial likelihood model on a large administrative dataset for West Germany to flexibly account for both unobserved individual heterogeneity and changes dependent on wages and children. We find that an average female childless worker is willing to give up daily exteuro0.27 per kilometre (0.4% of the daily wage) to reduce commuting distance at the margin. The average men's marginal willingness to pay is similar to childless women's over a large range of wages. However, women's marginal willingness to pay more than doubles after the birth of a child contributing substantially to the motherhood wage gap. A married mixed-sex couple's sample indicates that husbands try to avoid commuting shorter distances than their wives.
Keywords: C41; J13; J16; J31; J62; 330; commuting; marginal willingness to pay for job attributes; on-the-job search; Cox relative risk model; partial likelihood estimation; gender and parenthood in job search models; heterogeneity in job mobility; gender wage gap